2019
DOI: 10.1002/ps.5550
|View full text |Cite
|
Sign up to set email alerts
|

Self‐service traps inspected by avian and terrestrial predators as a management option for rodents

Abstract: BACKGROUND Worldwide, serval rodent species are major pests in agricultural landscapes. A vole‐specific tub‐trap combining trapping and natural predators was developed to minimize the migration of rodents into agricultural crops. The trap was tested in enclosures in terms of its trapability of common voles (Microtus arvalis Pallas) and in the field regarding predator access and removal of voles, both in comparison to a commercially available self‐service trap (standby‐box). RESULTS The trapability of voles was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…In addition, organic farming can minimize negative impact of voles in arable land by decreasing crop damage (Fisher et al, 2018). For example, Schlotelburg et al (2019) findings proved that self-service traps, which help reduce numbers of voles at arable land, are visited with higher probability at sites with characteristics of organic farming. On the contrary, Bruggisser et al ( 2010) claim that at organic vineyards, there is no positive effects on biodiversity nor abundance (studying plants, grasshoppers and spiders).…”
Section: Resultsmentioning
confidence: 93%
“…In addition, organic farming can minimize negative impact of voles in arable land by decreasing crop damage (Fisher et al, 2018). For example, Schlotelburg et al (2019) findings proved that self-service traps, which help reduce numbers of voles at arable land, are visited with higher probability at sites with characteristics of organic farming. On the contrary, Bruggisser et al ( 2010) claim that at organic vineyards, there is no positive effects on biodiversity nor abundance (studying plants, grasshoppers and spiders).…”
Section: Resultsmentioning
confidence: 93%
“…Babinska-Werka [31] found that an average vole population of 145-220/ha caused 8.7% damage to alfalfa crop. A significant level of crop protection is achieved by stimulating the presence of predators in the field [32]. Although acceptable protection is possible by applying other nonchemical measures [33][34][35], rodenticide treatments are still the most widespread and most frequent measure for controlling common voles in alfalfa crops, particularly in situations of great urgency to reduce vole numbers, i.e., in periods of their high abundance or seasons of overpopulation.…”
Section: Discussionmentioning
confidence: 99%
“…A very interesting method that could be implemented, even today in organic farming, is to create ditches around fields, with dug holes at distances of 4-5 m, where voles are caught [59,62]. Recently, this method was extended by Schlötelburg et al [77], who suggested a technique that combines mechanical and biological control by self-service traps that are inspected by avian and terrestrial predators. Such methods not only prevent the spread of voles from the infested field, but can also protect against reinfestation after treatment from the surrounding field.…”
Section: Agrotechnical Methods Of Control and Landscape Managementmentioning
confidence: 99%